Efficacy of the use of unaffected hand containment in unimanual intensive therapy to increase visuomotor coordination in children with hemiplegia: a randomized controlled pilot study - Rocío Palomo-Carrión; Elisabeth Bravo-Esteban; Sara Ando-La Fuente; Purificación López-Muñoz; Inés Martínez-Galán; Helena Romay-Barrero (SAGE Publishing, 2021)
Background: The capacity of children with hemiplegia to be engaged in anticipatory action planning is affected. There is no balance among spatial, proprioceptive and visual information, thus altering the affected upper limb visuomotor coordination. The objective of the present study was to assess the improvement in visuomotor coordination after the application of a unimanual intensive therapy program, with the use of unaffected hand containment compared with not using unaffected hand containment. Methods: A simple blind randomized clinical trial was realized. A total of 16 subjects with congenital infantile hemiplegia participated in the study with an age mean of 5.54 years old (SD:1.55). Two intensive protocols for 5 weeks of modified constraint-induced movement therapy (mCIMT) or unimanual therapy without containment (UTWC) were executed 5 days per week (2 h/day). Affected upper limb visuomotor coordination (reaction time, task total time, active range, dynamic grasp) was measured before-after intensive therapy using a specific circuit with different slopes (10°/15°). Results: Statistically significant inter-group differences were found after the intervention, with clinically relevant results for the mCIMT group not seen in UTWC, in the following variables: reaction time 10°slope ( p  = 0.003, d  = 2.44), reaction time 15°slope ( p  = 0.002, d  = 2.15) as well as for the task total time 10°slope ( p  = 0.002, d  = 2.25), active reach 10°slope ( p  = 0.002, d  = 2.7), active reach 15°slope ( p  = 0.003, d  = 2.29) and dynamic grasp 10°/15°slopes ( p  = <0.001, d  = 2.69). There were not statistically significant inter-group differences in the total task time with 15°slope ( p  = 0.074, d  = 1.27). Conclusions: The use of unaffected hand containment in mCIMT would allow improvements in the affected upper limb's visuomotor coordination. Thus, it would favor clinical practice to make decisions on therapeutic approaches to increase the affected upper limb functionality and action planning in children diagnosed with infantile hemiplegia (4-8 years old).